Edutainment Method Learning: Exploration of Variables and Implications on Children's Social Skills - Agustriana, Nesna; Kurniah, Nina; Alexon, Alexon; Kusumah, Raden Gamal Tamrin; Adiarti, Wulan (Al-Athfal: Jurnal Pendidikan Anak, 2022)
Purpose – The study aims to explore the differences in social skills between children who used the edutainment method with the game and a multimedia approach. Cards and treatment are the value of social skills in children’s reports.Design/methods/approach – The experimental method was designed with a treatment design one-shot case study. The pretest score was taken from the report cards that the child had previously received. Social skill score outcomes were taken after the treatment was completed.Findings – The results showed no significant differences in the social skills of children who were given the game approach edutainment method with children who were given the multimedia approach edutainment method. However, the average difference in the game approach and multimedia approach scores only has a value of 1,37500, so the difference is insignificant. These two treatments differ significantly from the child’s report card scores. The game approach has a difference of 4.27536 and sig 0.011 < 0.05; for the multimedia approach, it has a difference of 3.79167 and sig 0.028 <0.05. So it can be concluded that the edutainment method has a positive influence.Research implications/limitations – The teacher must know the child’s social skills so that he can choose the proper method of learning. The teacher must pay attention to the relationship between the characteristics possessed by each child and the learning method to be used. The teacher can use the game edutainment method in learning.Practical implications – Social skills can be built from several factors. The influencing factor is edutainment learning. This learning allows children to interact with other children and be able to re-communicate the activities they have done.Originality/value – This research is updated to explore the variables affecting children’s social skills. The independent variable used is the edutainment learning method with two approaches, namely multimedia and games. Paper type Research paper